The Effectiveness of Bullying and Violence Prevention: The Readiness of Universitas Terbuka Student Teachers for Safe Schools - Siswanto, Romi; Prasetya, Agus; Sambada, Dwi; Sulistiyono, Sulistiyono; Surami, Wuwuh Asrining (Educational Management, 2024)
This study aims to evaluate the readiness of prospective teachers at Universitas Terbuka in preventing bullying and violence in schools. The background of this research is driven by the high incidence of bullying in schools, which negatively affects student development. This research employs a mixed-method approach, collecting quantitative data through questionnaires and qualitative data through in-depth interviews. Participants consisted of 75 students in the quantitative survey and 25 students in the in-depth interviews. The results indicate that students have a good understanding of bullying and feel responsible for preventing it. There were no significant differences based on gender or semester, but there was a positive correlation between understanding of bullying and responsibility to prevent it. Participants also showed good skills in recognizing and handling bullying and felt supported by their schools. The main recommendations from this study are the need for more intensive training and stricter policies in bullying prevention. The implications of these findings suggest that ongoing support and effective policies are crucial for creating a safe and supportive school environment for all students